Analysis of Obstacles and Supporting Factors in English Learning for Adults - Moh. Ansori Dimastiar; Mochlis Ekowijayanto (Journal of General Education and Humanities, 2026)
English learning for adults plays a crucial role in supporting professional needs and self-development amidst the demands of globalization. However, adult learners often face various obstacles that can affect the success of their learning. This study aims to analyze the obstacles and supporting factors in English learning for adults in an integrated manner, taking into account the learners' real-life contexts. This study employed a qualitative approach with a descriptive qualitative design. Data were collected through semi-structured interviews with adult English learners participating in learning in non-formal and informal contexts, then analyzed using thematic analysis. The research findings indicate that the main barriers to English learning for adults include time constraints due to work and family demands, language anxiety impacting self-confidence, and linguistic difficulties related to distance from formal learning. Conversely, supporting factors such as motivation based on practical needs, social support, and the use of independent learning strategies and digital technology have been shown to help learners manage these barriers. This research confirms that barriers and supporting factors interact to shape the adult learning experience. These findings are expected to form the basis for developing English learning programs that are more flexible, contextual, and tailored to the needs of adult learners